Symbolic Interactionism and Consciousness in Axel Honneth’s Recognition Theory: Apprehending Self-Concept’s Distortion Post-Covid19 - Fatimah Fraya; Fristian Hadinata (Universitas Airlangga, 2025)
This article examines recognition of the self in symbolic interactionism, and how con-sciousness can apprehend distortions in self-concept, particularly after the social re-strictions during the Covid-19 pandemic. Through a literature review, a critical analy-sis method is carried out using a social epistemology approach to symbolic interaction-ism theory in social encounters with significant individuals and strangers, through un-derstanding the meaning derived from a number of intersubjectivities. Symbolic in-teractionism theory develops in various situations and levels of self-understanding, ranging from Herbert Mead’s the self to Erving Goffman’s concept of dramaturgy. These theories then provide an approach to how individuals in small-scale social struc-tures seek to be accepted within larger constructs. In line with this, the study aims to explain the capabilities of the self in society, which according to Axel Honneth will be influenced by the specific social group chosen, and the rules for engaging in it as an individual to play a role and be recognized for their achievements. The results of the study show how consciousness of concept of the self in symbolic interactionism can first find deep intersubjectivity and true meaning to be able to avoid distortions on a comprehensive path towards real self-recognition.